Numerical Simulation of H2O/LiBr Falling Film Absorption Process. (August 2015) - Zhang, Lianying; Wang, Yuan; Fu, Yongxia; Xing, Liu; Jin, Liwen
Abstract: Absorber is a critical component of an absorption air-conditioning system. Its performance influences directly the overall efficiency and volume. In this paper, the commercial simulation software CFD-FLUENT was used to simulate the falling film absorption process of the coolant LiBr/H2 O solution. This research attempts to know the effects of various Reynolds number on the absorption progress. The simulation results indicated that there was an optimized Reynolds number of liquid film which leads to an averaged maximum mass flux of 2.9×10 -3 kg·m -2 ·s -1 at the interface. The local interfacial mass transfer coefficient arrives at the maximum at the inlet, then decreases rapidly along the flow direction and approaches to a constant value gradually. It is also find that the local interfacial mass transfer coefficient increases with the increase of Reynolds number while the local heat transfer coefficient exhibits the opposite trend.